Inventory control model of a 4-Echelon production-distribution system - Tewary, Moumita; Das, Debabrata; Hui, Nirmal Baran (2017 IEEE International Conference on Industrial Engineering and Engineering Management (IEEM), 2017)
Present paper proposes a reorder interval-based mathematical model for a four-echelon inventory system of deterministic demand. It has four different echelons and 10 installations. The problem is posed as an optimization problem to determine the minimum inventory cost subject to different constraints. The model resulted in a mixed integer non-linear programming problem with some constraints. The optimal solution with lowest supply chain cost is obtained using an exhaustive search method. The best solution and corresponding variables are noted. Further Reorder intervals and lot-sizes of all installations are also determined in the paper.